1997
DOI: 10.1002/etc.5620160238
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three marine screening tests and four Oslo and Paris commission procedures to evaluate toxicity of offshore chemicals

Abstract: The results from the screening toxicity tests Artemia salina, Microtox®, and Mitochondria RET test were compared with those obtained from OSPAR (Oslo and Paris Commissions)‐authorized procedures for testing of offshore chemicals (Skeletonema costatum, Acartia tonsa, Abra alba, and Corophium volutator). In this study 82 test substances (26 non‐water soluble) were included. The Microtox test was found to be the most sensitive of the three screening tests. Microtox and Mitochondria RET test results showed good co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 2 publications
2
4
0
Order By: Relevance
“…Toxicity was not observed following exposure of this test species to the aqueous phases extracted from any of the three sediment samples tested. These results concur with the findings of Weideborg et al (1997) who also demonstrated A. salina to have too low a sensitivity to be considered as an appropriate bioassay organism for screening tests.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Toxicity was not observed following exposure of this test species to the aqueous phases extracted from any of the three sediment samples tested. These results concur with the findings of Weideborg et al (1997) who also demonstrated A. salina to have too low a sensitivity to be considered as an appropriate bioassay organism for screening tests.…”
Section: Discussionsupporting
confidence: 94%
“…Three bacterial bioassays were employed in this study, which allowed the toxicological assessment of both whole sediment (Microtox Ò Solid Phase Test (SPT), Toxi-ChromPad ä ) and sediment porewater and elutriates (Microtox Ò , MetPAD ä ). The marine diatom Skeletonema costatum was chosen to assess the acute toxicity of sediment porewater and elutriates due to its widespread distribution, sensitivity, and availability as an axenic culture (McKinney et al, 1997;Weideborg et al, 1997;Sverdrup et al, 2002). Sediment contamination has previously been investigated following exposure of S. costatum to both sediment porewater (Pederson et al, 1998) and elutriates (Cheung et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The Microtox ® test is considered relatively inexpensive, provides well-reproducible results, and offers a fast testing procedure. The toxicity data obtained with the Microtox ® test correspond well with acute toxicities obtained with standard toxicity tests for many bioassayed samples (Kaiser and Palabrica, 1991;Toussaint et al, 1995;Weideborg et al, 1997). This Microtox ® biotest has been widely used recently to investigate the toxicity of various inorganic and organic compounds in water samples (Trang et al, 2005;Gueune et al, 2009;Katritzky et al, 2010).…”
Section: Introductionsupporting
confidence: 64%
“…The algal test that primarily has been used for sediment toxicity testing is the standardized growth inhibition test using microalgae (ISO 2004(ISO , 2006 on elutriate water (e.g. Weideborg et al 1997;Pedersen et al 1998). The draw-back of using microalgae is that floating particles from the sediment may disturb the spectroscopic or fluorometric measurement.…”
Section: Discussionmentioning
confidence: 99%